Analisis Faktor Yang Mempengaruhi Beban Kerja Terhadap Kinerja Pegawai Pada Dinas Pengendalian Penduduk Dan Keluarga Berencana - Icha Nurfadilah Anwar; Uus Mohammad Darul Fadli (Masip: Jurnal Manajemen Administrasi Bisnis dan Publik Terapan, 2024)
This research aims to analyze the factors influencing workload on employee performance at the Office of Population Control and Family Planning (DPPKB). The background of this research is based on the importance of optimal employee performance in achieving organizational goals, while an imbalanced workload can hinder productivity. This study uses a qualitative method with a survey involving DPPKB employees as respondents. The findings indicate that factors such as working hours, attendance, and reporting targets of accountability letters significantly affect the workload, which in turn impacts employee performance. A supportive work environment and managerial support also play an important role in reducing workload pressure and enhancing performance. Additionally, the ability and skills of employees in managing complex tasks contribute to work effectiveness. The implications of this research suggest that management needs to conduct regular evaluations of workload distribution, provide a conducive work environment, and enhance support and skill development for employees. Thus, it is expected to create an optimal workload balance, which ultimately can improve employee performance and achieve organizational goals.